The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00253-019-10327-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies generated against dextransucrase exhibit potential anticariostatic properties in Streptococcus mutans

Abstract: Streptococcus mutans is a common principal causative agent of dental caries. In this communication, we describe that the antibodies raised against purified dextransucrase effectively inhibited the growth of S. mutans. The purified enzyme showed 58-fold enrichment, 17.5% yield and a specific activity of 3.96 units/mg protein. Purified IgG fraction of the antibody showed significant affinity with the antigenic protein. Immunotritation of the enzyme with dextransucrase antibody showed a gradual increase in inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 40 publications
(47 reference statements)
3
12
0
1
Order By: Relevance
“…Although showing promising anticaries effects, but their use was restricted of having cross reactivity with human heart tissues and skeleton muscles 52 . However western blot analysis revealed that antibodies against dextransucrase did not show any cross reactivity with human heart, liver, gall bladder and other mammalian tissues tested as described previously 16 . In the present study various human samples were tested for cross reactivity with dextransucrase antibody by immunohistochemistry which also showed negative results con rming no cross reactivity of dextransucrase antibodies with the human tissues.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Although showing promising anticaries effects, but their use was restricted of having cross reactivity with human heart tissues and skeleton muscles 52 . However western blot analysis revealed that antibodies against dextransucrase did not show any cross reactivity with human heart, liver, gall bladder and other mammalian tissues tested as described previously 16 . In the present study various human samples were tested for cross reactivity with dextransucrase antibody by immunohistochemistry which also showed negative results con rming no cross reactivity of dextransucrase antibodies with the human tissues.…”
Section: Discussionsupporting
confidence: 53%
“…Dextransucrase was puri ed to homogeneity from the culture supernatant of S. mutans MTCC-890 grown at 37 °C for 36 h by 55% ammonium sulphate precipitation followed by gel ltration chromatography using Sephadex G-200 and treatment with PEG-400 (polyethylene glycol 400) as reported earlier 16 .…”
Section: Bacterial Strain and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…indicated that dextransucrase antibodies inhibited acid production and reduced hydrophobicity of S. mutans , indicating the further enhancement of anticariogenic potential of dextransucrase antibodies. [ 51 ] Moreover, no cross-reactivity with dextransucrase antibody was seen indicating no harmful physiological effects in the humans. This has given the hope that effective, safer, and acceptable vaccines against human dental caries can be achieved in the near future.…”
Section: Anticaries Vaccinationmentioning
confidence: 99%